Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Can someone please help me with formatting this question?

$Y$ is an exponential random variable with parameter $1$. Let $Z=-Y$, what is the pdf of $Z$?


$$\Pr(-Y< y)=\Pr(Y>-y) ,$$


$$ \begin{align} f_Y(y)&=\frac{d}{dy}[ \Pr(Y>-y)]\\ &=\frac{d}{dy}[1-\Pr(Y< y]\\ &=\frac{d}{dy}[\exp(y)]\\ &=\exp(y) \end{align} $$

share|cite|improve this question
up vote 4 down vote accepted

Using theorem of transformation variables: $$ g_Z(z)=f_Y(y)\ |J|=f_Y(y)\ \left|\frac{dy}{dz}\right|, $$ where $J$ is Jacobian. We have $$ f_Y(y)=\lambda e^{-\lambda y}=e^{- y}\quad;\text{ since $\lambda=1$ and for }y\ge0 $$ and $y=-z$. Therefore $$ g_Z(z)=e^{- y} \left|\frac{dy}{dz}\right|=e^{-(-z)} \left|\frac{d}{dz}(-z)\right|=e^z\ |-1|=\Large\color{blue}{e^z}\quad;\text{ for }z\le0. $$ It can also be done as follows $$ \begin{align} \Pr[Z\le z]&=\Pr[-Y\le z]\\ &=\Pr[Y> -z]\\ &=1-\Pr[Y\le -z]\\ &=1-\left(1-e^{-(-z)}\right)\\ \Pr[Z\le z]&=e^{z}\\ \end{align} $$ and $$ \begin{align} f_Z(z)&= \frac{d}{dz}\Pr[Z\le z]\\ &=\frac{d}{dz}e^{z}\\ &=\Large\color{blue}{e^z} \end{align} $$

share|cite|improve this answer
The Jacobian, for $y\to-y$? Well... – Did Apr 21 '14 at 7:37
Is that something wrong that I don't notice @Did? – Tunk-Fey Apr 21 '14 at 7:43
Wrong? Did I say it was wrong? No, but a tad too complicated, if you ask me. – Did Apr 21 '14 at 9:02

We want $f_Z(z)$, the density function of $z$. We will first look for the cdf of $Z$.

When $z\gt 0$, we have $\Pr(Z\le z)=\Pr(Y\ge -z)=1$. So for $z\gt 0$, we have $F_z(z)=1$, and therefore $f_Z(z)=0$.

Now let $z\lt 0$. Then $$F_Z(z)=\Pr(Z\le z)=\Pr(Y\ge -z)=1-F_Y(-z).$$ Differentiate with respect to $z$, using the Chain Rule, and the fact that the derivative of $F_Y(y)$ with respect to $y$ is $e^{-y}$. We get $$f_Z(z)=-(-1)e^{-(-z)}=e^z.$$

Remark: It may be a little clearer to note that $F_Y(y)=1-e^{-y}$, so if $z\lt 0$ then $$F_Z(z)=1-F_Y(-z)=1-(1-e^{-(-z)})=e^z,$$ and therefore $f_Z(z)=e^z$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.